Genetic variability of Appaloosa horses: A study of a closed breeding population from Argentina - Corbi Botto, Claudia Malena (2014)
The genetic diversity and structure of 72 Appaloosa horses belonging to a closed breeding population from an ecological reserve in Buenos Aires, Argentina, was investigated using eight microsatellite markers from the International Society for Animal Genetics panel. Our data showed that this Appaloosa horse population had an elevated degree of genetic diversity (He = 0.746) and did not present a significant increase of homozygous individuals (FIS~0). However, the short tandem repeats, AHT5, ASB2, HTG10 and VHL20, were not in Hardy-Weinberg equilibrium (P-value < 0.05). Genetic relationships between this population and other well known horse breeds showed that Appaloosa horses from Argentina could have had their origin in the horses of the Nez Perce's people in Idaho while other Appaloosa horses may have had influences from Andalusian and Lusitano breeds. This closed breeding population conserves an important degree of Appaloosa genetic diversity and notwithstanding its particular breeding characteristics, represents a valuable genetic resource for conservation.